The economics of change and stability in social trust: Evidence from (and for) Catalan secession. (27th July 2021) - Bjørnskov, Christan; Borrella‐Mas, Miguel Ángel; Rode, Martin
Abstract: Consequences of social trust are comparatively well studied, while its societal determinants are often subject to debate. This paper studies both in the context of Catalan attempts to secede from Spain: First, we test whether Catalonia enjoys higher levels of social capital that it is prevented from capitalizing on. Second, the paper examines whether secessionist movements create animosity and political divisions within society that undermine trust. Employing the nine available waves of the European Social Survey for Spain, we only find weak indications that social trust levels are higher in Catalonia than in the rest of the country. Interestingly, we further find testimony of a purely transient "exuberance effect" after secession became a real option, indicating that the long‐run evolution of social trust may best be thought of as a stable punctuated equilibrium.